(3GdhGLHGJ GdGbUGOjI ddOhdI aj Xd GdeSJLOGJ GdYGdejIs - (3GdYQHj(B, (3Zhjfjs ((3GdLRGFQ(B:s (3GdecJH GdLGeYj GdMOjK,s, 2016)
(3GSJgd GdeDda cJGHg HJhWFI Ydi eQGMd JWhQ GdGbJUGO GdLRGFQj Ke Jcde aj GdeMhQ GdGhd Ydi hGLHGJ GdOhdI GdGbJUGOjI aj GdacQ GdGbJUGOj , hGLHGJ GdOhdI GdGbJUGOjI aj GdacQ GdGbJUGOj GdGSdGej hGdGTJQGcj ,aj GdacQ GdQCS eGdj, aj acQ GdWQjb GdKGdK haj GdeMhQ GdKGfH JMOK Yf hGbY GdGbJUGO GdLRGFQj hMbjbI GdJMhdGJ GdQGgfI , hGbY GdGbJUGO GdLRGFQj ef NdGd GdGMUGFjGJ hGdeDTQGJ , GdJMhdGJ GadQGgfI aj GdYGde hCKQgG Ydi GdGbJUGO GdLRGFQj , GdMdhd GdebJQMI , GdOhQ GdGbJUGOj GdLOjO ddOhdI , YfGUQ GdJMhd aj OhQ GdOhdI , GUdGM HjFI GdeDSSI ddGYeGd hJfGaSjI GdGbJUGO GdLRGFQj , GdfehPL GdebJQM dGUdGM GdfXGe GdeGdj (B"(3GdeUQaj GdVQjHj hGdJLGQj GdLRGFQ (B"(3, GSJQGJLjI GdTQGcI Hjf GdbWGY GdMchej hGdbWGY GdNGU (B.s
(3HjHdjhZQGajG U(B. 197s
Keywords: (3GdGbJUGOs; (3GdLRGFQ (B-(3GbJUGOs